2017
DOI: 10.22489/cinc.2017.360-239
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Feature Based Classifiers and Convolutional Neural Networks to Detect Arrhythmia from Short Segments of ECG

Abstract: The diagnosis of cardiovascular diseases such as atrial fibrillation (AF) is a lengthy and expensive procedure that often requires visual inspection of ECG signals by experts. In order to improve patient management and reduce healthcare costs, automated detection of these pathologies is of utmost importance.In this study, we classify short segments of ECG into four classes (AF, normal, other rhythms or noise) as part of the Physionet/Computing in Cardiology Challenge 2017. We compare a state-of-the-art feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 18 publications
1
113
1
Order By: Relevance
“…With the initialization of variables W 0 and P 0 , we can apply the alternative optimization method to solve Eq. (8). When the value of W is fixed, the optimal P can be obtained by minimizing the following function:…”
Section: B the Iterative Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…With the initialization of variables W 0 and P 0 , we can apply the alternative optimization method to solve Eq. (8). When the value of W is fixed, the optimal P can be obtained by minimizing the following function:…”
Section: B the Iterative Proceduresmentioning
confidence: 99%
“…Once this is done, the similarity matrix W can be optimized by solving (15). We repeat the iterative procedure to update the above variables until the optimization problem (8) converges to the local minimum. The details of the complete optimization procedure are summarized in Algorithm 1.…”
Section: B the Iterative Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, many other participants of the Challenge also used neural networks [13,14,15,16] as feature detector in addition to their traditional feature extractors. One of them was Andreotti et al [17], who compared their featurebased classifiers to residual neural networks. They concluded that their neural networks outperform their featurebased classifiers, showing the strength of the purely neural network-based approach.…”
Section: Related Workmentioning
confidence: 99%
“…Some relevant algorithms for the detection of AF are the ones based on the analysis of the P-wave [10,11], or those that utilize a large set of features obtained from ECGs in an artificial neural network [12][13][14] or in a deep learning approach [15,16]. Furthermore, it is worth mentioning that several recent clinical trials on large populations focusing on AF detection have been carried out [17][18][19].…”
Section: Introductionmentioning
confidence: 99%